Induced labour in pregnancy with congenital abnormalities: clinical indications or patient demand - Pribadi, Adhi (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2022)
Congenital abnormalities are a nightmare for a pregnant woman. However, congenital abnormalities are divided into several conditions. The state of major disability is the worst situation, with the possibility of disability and even postpartum death. The disability is still a pregnancy that can cause complications that have a bad effect on the mother, so the pregnancy is often induced labor for fear of endangering the mother even though the complications have not yet appeared. In addition, it often happens because the family refuses the presence of a child with a disability. Criteria and references for intrauterine anomalies have been made by various countries and organizations, with the treatment taking into account clinical, psychosocial, religious, and legal aspects. However, this reference is not always easy to implement due to various factors, so that the decision to induced labor or induced abortion is always based on the advice of the medical team and family approval without leaving the legal aspect. Parental consent is important because not all pregnant women agree to induced labor of pregnancy even though it is a major disability and threatens postpartum death. On the other hand, if the defect can be corrected, then a clinician must be able to maintain the pregnancy and refuse unnecessary attempts to terminate the pregnancy.